ANALISIS POTENSI DIRI MAHASISWA TERHADAP MINAT MENJADI GURU MATEMATIKA - Datu, Rianto Pali'; Ruslau, Maria Fransina Veronica; Suryani, Dessy Rizki (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
The purpose of this study is to analyze and describe students' self-potential from the potential sources of IQ and potential EQ for interest in becoming mathematics teachers. The method used in this study is a qualitative descriptive method with the subject of this research being students majoring in mathematics education who collect 87 students. The technIQue of collecting data using tests and filling out questionnaires. The test is used to obtain student IQ data, while filling out the questionnaire sheet is used to obtain EQ data and students' interest in becoming a teacher. Data acquisition through tests and questionnaire filling is done online by using the help of Google Form media. Based on the results of data processing there are still students who are lacking in terms of IQ, but students have a good EQ with considerable interest in the teaching profession. Good student EQ through self-awareness contributed 60%, independent students contributed 51%, student motivation contributed 92%, student empathy contributed 89%, and students' social skills contributed 69%. Besides that students' interest to become teachers is approved through awareness, emotions, and conation. Student cognition contributed 94%, student logistics contributed 93%, and contribution or contribution 62%. Thus it can be concluded that mathematics education students are quite ready to become a teacher